(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Abdurahman Jami, the leader of the Naqshbandiyya sect, and Alisher Navoi, his disciple, were of the same mind not only in creativity, but also in profession. Therefore, the idea of a perfect person is reflected in the essence of all the works created by them. In particular, the same can be said about the thinkers’ epics “Khiradnomai Iskandari” and “Saddi Iskandari”. This article talks about the essence of the concept of satisfaction in epics.